The sustainability of reforesting landscapes with exotic species: a case study of eucalypts in Ethiopia - Belay Zerga; Bikila Warkineh; Demel Teketay; Muluneh Woldetsadik (Sustainable Earth Reviews, 2021)
Abstract Eucalypt reforestation has been a common feature of many countries, especially in the developing countries, such as Ethiopia. Farmers in Ethiopia plant large numbers of eucalypts on small areas of land and manage them to yield a variety of products, including leaves and small branches for fuelwood, and poles and posts for house building and other farm uses. Many people in Ethiopia are dependent on eucalypts as a source of fuel and house building material. The use of trees, especially eucalypts, as a living bank account, to be harvested when there is a need for cash, is widespread. This being the reality, the arguments for and against planting eucalypts in Ethiopia has been mounting from time to time, especially associated with water use, soil fertility, soil erosion, allelopathic effects, understory vegetation and plant diversity as well as wild animals. The paradox of reforestation using eucalypts results, mostly, from inappropriate species-site matching and poor management rather than the inherent biological characteristics of the species. Therefore, the debate on eucalypts under the pretext of concern for indigenous species and natural forests should shift to how both plantations established using eucalypts and indigenous species as well as natural forests can help in the enhancement of the socio-economic development and environmental conservation of countries, such as Ethiopia. Despite the claimed negative impacts of eucalypts, farmers in Ethiopia have utilized their traditional knowledge and experience in establishing and managing eucalypt stands. In addition, the available reports in Ethiopia are in favour of planting eucalypts since the authors acknowledge that: (i) the negative impacts can be minimized provided that the choice of species and site as well as the management of the stands are appropriate, (ii) the benefit derived can offset the losses that can occur from such plantations, (iii) no other species seems to replace them to bridge the ever-widening gap between demand and supply of wood and (iv) the profit derived from eucalypt plantations is considerably higher than cultivating crops. However, the choice of eucalypt species should be based on many criteria, for example maximum wood production, ecological sustainability, marketability of the planted species and usefulness of the species to the local populations. All these criteria involve not only a choice of species planted, but also a choice of plantation management methods from initial planting to final cutting of the trees. Careful selection of appropriate species and matching them with appropriate sites must be taken as prerequisite, and the right management practices should be employed.